(untitled) (Journal of the Bangladesh Agricultural University, 2018)
The present study was conducted to assess the harvesting procedures, nutritional value of stingray in the coastal district Cox’s Bazar, Bangladesh and its utilization as value-added product. Data were collected through direct observation, focus group discussion, questionnaire interview and cross check interview. It was found that stingray was mainly caught by artisanal fishery using gill net, set bag net and long line within 5-40 m depth ranges about 100-200 km at west direction, 10-60 km at south direction and 50-100 m depth ranges about 60-100 km at southwest direction from Fishery ghat, Cox’s Bazar. In the west direction, stingray harvesting grounds were Sonar char, Rupar char, Char Gongmoti and Dublar char in Patuakhali district, and Cox’s Bazar coast, Teknaf coast, St. Martin’s island coast and the south patches at south direction and middle ground at southwest direction. Generally stingrays was harvested throughout the year but were abundant during December and January. At fish landing center, the supply chain of stingray from fishermen to consumers passed through a number of intermediaries e.g., dealer, wholesaler, retailer and supplier. The market value of stingray varied where fishermen sold at 90-140 Tk/kg that passed through these channels and at last consumers got it at 140-250 Tk/kg. Six species of stingray were found in Fishery ghat, Cox’s Bazar namely Himantura gerrardi, Dasyatis bennetti, Himantura uarnak, Himantura undulata, Himantura bleekeri and Neotrygon kuhlii. Among them H. gerrardi and H. bleekeri were available and very popular in the market. The average moisture, protein, lipid, carbohydrate and ash content of H. bleekeri were determined as 78.08%, 14.80%, 4.31%, 0.95% and 1.87%, respectively and total energy content 103.78 Kcal. Three utilization processes were investigated in this study namely fish ball of stingray, stingray recipe with sour of tomato and stingray recipe with sour of tamarind. Fish ball was preferred as an excellent product and others were as very good products. Dried stingray products were only utilized by tribal peoples. Dried meat, skin and spine were exported abroad namely to China, Thailand, Myanmar and Singapore. J. Bangladesh Agril. Univ. 16(3): 539–544, December 2018